2017
DOI: 10.1002/ams2.260
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected complications immediately after cranioplasty

Abstract: CaseAn 84‐year‐old man with subarachnoid hemorrhage underwent craniotomy and clipping with external decompression. Perfusion magnetic resonance imaging showed subclinical sinking skin flap syndrome, and he underwent cranioplasty on postoperative day 58. No problems occurred during the operation, but cerebral edema and hemorrhage were recognized on immediate postoperative computed tomography. Edema continued to progress, but edema and bleeding eventually improved without additional surgery.OutcomeNeurological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Wang et al 18 reported for the first time that ipsilateral intracranial vasculopathy is a risk factor for malignant cerebral swelling after cranioplasty. Kato et al 19 support the hypothesis that cerebral swelling after cranioplasty is probably due to the reduction of autoregulation, reperfusion, venous stasis, negative pressure due to a subgaleal suction drain, vascular damage following the restoration of midline shift, sinking skin flap syndrome, and allergic reaction. We believed that the following factors might have played a role in our patient:…”
Section: Discussionmentioning
confidence: 90%
“…Wang et al 18 reported for the first time that ipsilateral intracranial vasculopathy is a risk factor for malignant cerebral swelling after cranioplasty. Kato et al 19 support the hypothesis that cerebral swelling after cranioplasty is probably due to the reduction of autoregulation, reperfusion, venous stasis, negative pressure due to a subgaleal suction drain, vascular damage following the restoration of midline shift, sinking skin flap syndrome, and allergic reaction. We believed that the following factors might have played a role in our patient:…”
Section: Discussionmentioning
confidence: 90%
“…This condition counts amongst the less frequent postoperative complications and is most likely explainable as the consequence of a reperfusion injury (11,42). As already mentioned, autoregulatory mechanisms of the intracranial space are impaired during the post-craniectomy period, often associated with a cerebral hypoperfusion and sinking skin fl ap syndrome (8,11,12). After a longer period, during which the brain was almost directly exposed to atmospheric pressure, the pressure was rapidly alleviated after a cranial vault reconstruction.…”
Section: Discussionmentioning
confidence: 94%
“…A restoration of cranial vault has a potential to normalize cerebrospinal fl uid circulation and to avoid the need for shunt procedure due to hydrocephalus, factor associated with a worse neurological outcome (13,15,16). Also, it has been described, that in patients after craniectomy, a decreased perfusion and metabo-lism with an associated possible neurological dysfunction occur, often accompanied by "sinking skin fl ap" (7,8,11,12,17). Besides of this, oedema and penetration of cerebrospinal fl uid into post-contusion foci with a subsequent worsening of motor functions was described as "motor trephine syndrome".…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations